Underground temperature background of the Saksagan iron ore region in Kryvyi Rih basin - Y. P. Mechnikov; S. V. Tikhlivets; O. G. Volkov (Геофизический журнал, 2019)
The data from thoroughly selected 46 deep exploration boreholes drilled along the Saksagan iron ore stripe located in the Kryvbas and a transverse section of the stripe, which included results of studies conducted in the Kryvyi Rih super-deep borehole SD-8, have served as the data bank for analyzing and calculating the temperature background parameters. The methodical procedures for ordinary measurements averaging, determining and generalizing temperature values and other thermal background parameters were given.